2023
DOI: 10.1002/smll.202305548
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in 2D Metal‐Organic Framework‐Related Materials

Yun Xie,
Xinyue Wu,
Yuxin Shi
et al.

Abstract: Abstract2D metal‐organic frameworks‐based (2D MOF‐related) materials benefit from variable topological structures, plentiful open active sites, and high specific surface areas, demonstrating promising applications in gas storage, adsorption and separation, energy conversion, and other domains. In recent years, researchers have innovatively designed multiple strategies to avoid the adverse effects of conventional methods on the synthesis of high‐quality 2D MOFs. This review focuses on the latest advances in cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 242 publications
(327 reference statements)
0
5
0
Order By: Relevance
“…Compared to three-dimensional metal−organic frameworks, two-dimensional metal−organic framework (2D MOF) nanosheets offer distinct advantages, such as a higher density of surface-active sites, a larger specific surface area, shorter diffusion pathways, and a more rapid electron transfer rate. 11,12 Consequently, they are crucial precursors for the cathode catalysts in zinc−air batteries. 13,14 Within the category of 2D MOF nanosheets, the 2D fluorinated metal−organic framework nanosheets comprise a cubic topology that results from a 3D inorganic anionic column composed of metal ions as a support, interconnected with organic ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to three-dimensional metal−organic frameworks, two-dimensional metal−organic framework (2D MOF) nanosheets offer distinct advantages, such as a higher density of surface-active sites, a larger specific surface area, shorter diffusion pathways, and a more rapid electron transfer rate. 11,12 Consequently, they are crucial precursors for the cathode catalysts in zinc−air batteries. 13,14 Within the category of 2D MOF nanosheets, the 2D fluorinated metal−organic framework nanosheets comprise a cubic topology that results from a 3D inorganic anionic column composed of metal ions as a support, interconnected with organic ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to three-dimensional metal–organic frameworks, two-dimensional metal–organic framework (2D MOF) nanosheets offer distinct advantages, such as a higher density of surface-active sites, a larger specific surface area, shorter diffusion pathways, and a more rapid electron transfer rate. , Consequently, they are crucial precursors for the cathode catalysts in zinc–air batteries. , Within the category of 2D MOF nanosheets, the 2D fluorinated metal–organic framework nanosheets comprise a cubic topology that results from a 3D inorganic anionic column composed of metal ions as a support, interconnected with organic ligands . These MOF nanosheets offer versatile possibilities in network chemistry and diverse structural units of inorganic molecules, which can be exploited to introduce the ligand-unsaturated metal active sites required for various reactions into the porous fluorinated metal–organic framework nanosheets .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of experimental studies have demonstrated the possibility of efficient utilizing MOFs for coherent light emission in the laser regime [8][9][10], coherent and incoherent light conversion [11][12][13][14], white light [15] and quantum light emission [16,17], nonlinear optical absorption [18][19][20][21] and encryption [22][23][24], as well as for optical data transferring [25][26][27][28][29] even at ultrafast regime [30,31]. In most of the above cases, MOFs can be considered as competitive or even superior to commercial NLO crystals, combining it with the simplicity of their synthesis and scalability [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Their ultrathin thickness, large surface area, and high surface-to-volume atom ratios set them apart from 3D MOFs. 37,38 When compared with their 3D counterparts, 2D MOFs exhibit superior drug loading efficiency and reaction activity, making them particularly suited for bio-application, especially specialized cancer treatments. 39 As we summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%